2010
DOI: 10.1016/s1674-8301(10)60058-9
|View full text |Cite
|
Sign up to set email alerts
|

MiR-181b suppresses proliferation of and reduces chemoresistance to temozolomide in U87 glioma stem cells

Abstract: MicroRNAs regulate self renewal and differentiation of cancer stem cells. There, we sought to identify the expression of miR-181b in glioma stem cells and investigate the biological effect of miR-181b on glioma stem cells in this study. MiR-181b expression was measured by real-time PCR in glioma stem cells isolated from U87 cells by FACS sorting. After miR-181b was overexpressed in U87 glioma stem cells by miR-181b lentiviral expression vector and/or treatment of temozolomide, secondary neurosphere assay, soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…GBM is characterized by complex tissue heterogeneity, in which there is a class of stem cell-like tumor-initiating cells, called GSCs, which have the ability to self-renew, grow continuously and differentiate into multiple neural cell types [34][35][36]. Further studies found that GSCs are key factors leading to the occurrence, recurrence, treatment tolerance and poor prognosis of glioma [35,[37][38][39][40]. We successfully propagated eight human GSC lines with four different molecular subtypes and found the highest PSAP expression and secretion in mesenchymal GSCs, as determined by western blotting and ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…GBM is characterized by complex tissue heterogeneity, in which there is a class of stem cell-like tumor-initiating cells, called GSCs, which have the ability to self-renew, grow continuously and differentiate into multiple neural cell types [34][35][36]. Further studies found that GSCs are key factors leading to the occurrence, recurrence, treatment tolerance and poor prognosis of glioma [35,[37][38][39][40]. We successfully propagated eight human GSC lines with four different molecular subtypes and found the highest PSAP expression and secretion in mesenchymal GSCs, as determined by western blotting and ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…With this knowledge, microRNAs reported to influence TMZ resistance in GBM (miR-195, miR-455, miR-10 (Ujifuku et al 2010), miR-181b (Li et al 2010; Slaby et al 2010), miR-21 (Shi et al 2010a; Wong et al 2012), miR-125b (Shi et al 2012), miR-145 (Yang et al 2012), miR-211 (Asuthkar et al 2012), miR-17 (Comincini et al 2013), miR-9 (Munoz et al 2013), the miR-183/96/182 cluster (Tang et al 2013), and miR-221/222 (Chen et al 2012c)) were shown to target pathways involved in proliferation, apoptosis, and stem cell maintenance. Some studies suggested that targeting GSCs may effectively reduce tumor recurrence and significantly improve GBM sensitization to radiation (Huang et al 2010).…”
Section: Micrornas In Brain Tumorsmentioning
confidence: 99%
“…Many miRNAs have been proved to be proto-oncogenes or tumor suppressors in various human cancers, including in glioma. [3][4][5] Recent studies have revealed that miRNAs, such as miR-7, 6, 7 miR-124, [8][9][10] miR-128, 11 miR-107, 12 and miR-181b, [13][14][15] are globally dysregulated in glioma. However, the particular molecular mechanisms through which miRNAs mediate glioma carcinogenesis and metastasis are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%